GAZE BEYOND THE BOUNDARIES: TRANSCENDING THE HURDLES IN MANAGING GRAVES OPHTHALMOPATHY IN A DISTRICT HOSPITAL SETTING - Marimuthu, Surendran; Zuki, Nor Izzati Moh; Tubillah, Noor Fariha Mohd; Tatt, Teoh Aik (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Graves ophthalmopathy (GO) is an autoimmune condition characterized by inflammation and tissue expansion within the orbit. The pathogenesis of GO involves complex interactions between autoantibodies, inflammatory mediators, and orbital fibroblasts. GO affects both the soft tissues and the extraocular muscles, leading to a range of ocular manifestations, including proptosis, eyelid retraction, diplopia, and in severe cases, vision loss. CASE An 18-year-old female, a passive smoker with no significant medical history, presented to a district hospital with sudden onset of exophthalmos, eye discomfort, and double vision persisting for three weeks. She has a strong family history of thyroid disease. Physical examination revealed the patient to be in a state of thyroid storm and a clinical activity score (CAS) of 3. The ophthalmologic evaluation revealed bilateral proptosis, conjunctival injection, and restricted extraocular movements consistent with GO. Laboratory investigations confirmed hyperthyroidism. Orbital CT demonstrated enlargement of the extraocular muscles and expansion of orbital fat, further supporting the diagnosis of GO. The patient was promptly initiated on treatment for thyroid storm, including antithyroid medications and supportive care to stabilize thyroid function. Systemic corticosteroids and lubricating eye drops were administered to alleviate ocular symptoms. With aggressive medical management, the patient’s thyroid storm resolved, and ocular symptoms showed significant improvement throughout treatment. CONCLUSION This case highlights the importance of considering GO in the differential diagnosis of patients presenting with exophthalmos and ocular symptoms, especially when complicated by thyroid storm. Early recognition and collaborative management are essential for optimizing outcomes in such cases.